2012
DOI: 10.1259/bjr/61380797
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic cancer surveillance following whole-gland high-intensity focused ultrasound: comparison of MRI and prostate-specific antigen for detection of residual or recurrent disease

Abstract: Objective: This retrospective study compares dynamic contrast-enhanced (DCE) MRI with the serial prostate-specific antigen (PSA) measurement for detection of residual disease following whole-gland high-intensity focused ultrasound (HIFU) therapy of prostate cancer. Methods: Patients in whom post-HIFU DCE-MRI was followed within 3 months by ultrasound-guided transrectal biopsy were selected from a local database. 26 patients met the study inclusion criteria. Serial PSA levels following HIFU and post-HIFU follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 19 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…Sensitivity ranged between 73% and 87% between 3 readers, whereas specificity ranged between 73% and 82%. These results were comparable with pre-biopsy PSA levels [42]. …”
Section: Imaging For Follow-upsupporting
confidence: 78%
“…Sensitivity ranged between 73% and 87% between 3 readers, whereas specificity ranged between 73% and 82%. These results were comparable with pre-biopsy PSA levels [42]. …”
Section: Imaging For Follow-upsupporting
confidence: 78%
“…Fourthly, not all patients received postoperative biopsies as these were only carried out on a ''for-cause'' basis due to rising PSA or a prostate MRI suggestive of residual or recurrent disease. Our previous report has showed that such a strategy was accurately valid [9]. Finally, there was a significant rate of retreatment that many would argue is a weakness, although the ability to re-apply the same treatment might be considered an advantage.…”
Section: Limitationsmentioning
confidence: 99%
“…Two rises in PSA after nadir, without predefining the level of rise, was investigated with a prostate biopsy or MRI followed by biopsy if the MRI was suspicious[9]. All centres and surgeons underwent a rigorous period of training and proctoring by expert HIFU operators involving online learning, observation of at !5 cases on two separate occasions in an expert centre and on-site proctoring by an expert urologist for !5 cases followed by the presence of a senior expert clinical applications specialist for all subsequent treatments.…”
mentioning
confidence: 99%
“…Multiple MRI protocols can be proposed for the guidance of ultrasound therapies including diffusion-weighted (75, 76), T2-weighted (77, 78), and contrast enhanced T1-weighted imaging (7981), fluid attenuated inversion recovery (FLAIR) (82), heteronuclear ( 23 Na) (83), spectroscopy (84), and displacement sensitive sequences via MR elastography (85). Following HIFU ablation of the prostate, gadolinium enhanced MRI is often used to evaluate the extent of tissue damage.…”
Section: Application Of Imaging Technologymentioning
confidence: 99%